Effect of support based on family centered empowerment model on care burden in family caregivers of patients with multiple sclerosis - Farshid Mohammad Mousaei; Seyedmohammad Mirhosseini; Mohammad Hossein Mafi; Nevin Günaydın; Hamid Reza Zendehtalab (Frontiers Media S.A., 2023)
IntroductionFamily caregivers of patients with multiple sclerosis (MS) are at risk of care burden that may lead to a detrimental effect on their quality of life (QoL), physical and mental well-being. This study aimed to determine the effect of the family-centered empowerment model (FCEM) on the care burden of caregivers of patients with MS.MethodsThis quasi-experimental study was conducted using convenience sampling on 60 caregivers of patients referring to the Multiple Sclerosis Clinic in Ghaem Hospital, Mashhad, Iran. The participants were assigned to FCEM and control groups based on the days they were referred to the MS clinic. Data collection tools included the Zarit Caregiver Burden Inventory (CBI), completed in the intervention and control groups before and 1 month after the intervention. The support based on FCEM was provided during eight 45-60-min sessions, and the control group received the medical center's routine training. Data were analyzed by Chi-square, independent t-test, analysis of covariance, and repeated measure tests.ResultsThe results of the present study showed that all demographic characteristics were homogeneous at the baseline. Before the intervention, no significant difference was observed between the two groups regarding mean scores of care burden. Based on the repeated measure test, there was no significant treatment and time interaction in changes in care burden.ConclusionThe FCEM has no significant effect in alleviating the care burden. It is recommended to observe the necessary considerations regarding the context of this type of intervention and to carry out further investigations in different intervals.